1989
DOI: 10.1093/bja/62.6.637
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Anterior Approach to the Coeliac Plexus Using Ultrasound

Abstract: A new approach is described to the neurolytic block of the coeliac plexus through the anterior abdominal wall using ultrasonic guidance. In nine patients, ultrasound was used for needle placement and examination of the spread of injection. Total pain relief was obtained in seven of the patients after 2 weeks and in five patients after 6 months. No serious complications were observed. The anterior approach is simple and useful in those patients with chronic pancreatic pain undergoing biopsy of the pancreas, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Hence fluoroscopy, CT, EUS (endosonographically) or USG guidance is essential for proper demonstration of celiac plexus and appropriate deposition of local anaesthetics. 6 These may be the reasons for CPB not being popular among anaesthesiologists as sole technique for surgical anaesthesia. Currently, the technique is mainly limited to palliative analgesic care for abdominal cancer pain and chronic pancreatitis.…”
Section: Journal Of Society Of Anesthesiologists Of Nepalmentioning
confidence: 99%
“…Hence fluoroscopy, CT, EUS (endosonographically) or USG guidance is essential for proper demonstration of celiac plexus and appropriate deposition of local anaesthetics. 6 These may be the reasons for CPB not being popular among anaesthesiologists as sole technique for surgical anaesthesia. Currently, the technique is mainly limited to palliative analgesic care for abdominal cancer pain and chronic pancreatitis.…”
Section: Journal Of Society Of Anesthesiologists Of Nepalmentioning
confidence: 99%
“…26 This is understandable because the general condition of many of these patients is poor, and blood pressure and ECG monitoring and even assisted ventilation are often necessary. 27 The anterior approach also obviates transcrural placement of the needle, which may sometimes require the abdominal aorta to be crossed to achieve efficient spreading of neurolytic agent.…”
Section: Anterior Approachmentioning
confidence: 99%
“…Six patients had increased peristalsis, but this did not last more than 48-72 h. They concluded that an anterior approach was useful in patients with chronic pancreatic pain undergoing biopsy of the pancreas, and in terminally ill or heavily sedated patients who had difficulty in tolerating the prone flexed position. 27 Romanelli et al in 1992 evaluated the efficacy of CT-guided coeliac plexus neurolysis with 20 ml of absolute alcohol by an anterior approach in 17 patients with chronic abdominal pain suspected to be of coeliac ganglion origin. Pain relief was graded from 1+ (no change) to 4+ (complete relief ).…”
Section: Ultrasound Guidancementioning
confidence: 99%
“…The theoretical advantages of the abdominal anterior approach include reduced discomfort during the procedure by avoiding a prolonged prone position and other benefits associated with a supine position (e.g., easier sedation for those who are at risk and require meticulous monitoring and good ventilation. 3 We describe CT-guided neurolytic splanchnic nerve block using an anterior approach in patients scheduled for celiac plexus block, in whom distorted anatomy prevented the traditional celiac plexus neurolysis.…”
Section: Ct-guided Neurolytic Splanchnic Nerve Block By An Anterior Approachmentioning
confidence: 99%